First person - Conor McGrath (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Conor McGrath is first author on ' Development of a novel human intestinal model to elucidate the effect of anaerobic commensals on Escherichia coli infection', published in DMM. Conor conducted the research described in this article while a PhD researcher in Stephanie Schüller's lab at the University of East Anglia, Norwich, UK. He is now a fermentation technician in the lab of Shane Gaudin at Lysine Australia, Tingalpa, Australia, investigating the harnessing of microbes to benefit human health and biotechnology.